2021
DOI: 10.1177/10547738211002021
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a Child with Cancer: Experiences of Jordanian Mothers

Abstract: The diagnosis of childhood cancer is one of the most serious and unexpected experiences a mother can endure. A descriptive phenomenological approach was used to explore the experiences of mothers of children diagnosed with cancer in Jordan. Themes that emerged include (1) Emotional response on knowing the diagnosis (feelings of shock, lack of preparedness, denial, and feelings of “paralysis”), (2) Fear of the dreaded disease (fear of suffering and fear of death), and (3) The challenges of the treatment journey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The studies were all conducted on parents who were taking care of children with leukemia, according to an analysis of ten articles that fit the criteria (Cornelio et al, 2016;Lambert et al, 2021;Pannier et al, 2019;Peikert et al, 2020;Pishkuhi et al, 2018;Raber et al, 2020;Shattnawi et al, 2021;Supriatin & Oktaviani, 2019;Van Schoors, De Paepe, et al, 2019;Verberne et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were all conducted on parents who were taking care of children with leukemia, according to an analysis of ten articles that fit the criteria (Cornelio et al, 2016;Lambert et al, 2021;Pannier et al, 2019;Peikert et al, 2020;Pishkuhi et al, 2018;Raber et al, 2020;Shattnawi et al, 2021;Supriatin & Oktaviani, 2019;Van Schoors, De Paepe, et al, 2019;Verberne et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are variations in how the age of the family (parents) and the children is classified, all reviews in this body of literature employ families (parents) that have pediatric leukemia patients as the subject of research. research carried out by (Shattnawi et al, 2021) parents using age > 20 years. Research (Lambert et al, 2021;Pannier et al, 2019;Peikert et al, 2020;Pishkuhi et al, 2018;Van Schoors, De Paepe, et al, 2019;Verberne et al, 2019) parents in the age spectrum 33-52 year.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The possible explanations might be that the parents might face the challenge of the care process for childhood and adolescence patients with osteosarcoma, including financial difficulties, patients' feeling of social isolation by their peers, and role transition; therefore, the anxiety and depression of the parents might continue to deteriorate. [24] In terms of the risk factors of anxiety and depression among parents of children with cancer, previous studies have reported that economic fragility, unemployment, parental fear of progression are correlated with elevated incidence of anxiety and depression among parents of children with blood cancer and central nervous system cancer. [19,21] In the current study, factors related to the risk of anxiety and depression among parents of childhood and adolescence patients with osteosarcoma were explored, which presented that the role of the mother in parents' relation, divorced or widowed marital status of parents, higher Enneking stage of patients, amputation as surgery of patients were independently correlated with increased risk of anxiety, while elevated family annual income was independently correlated with declined risk of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations might be that the parents might face the challenge of the care process for childhood and adolescence patients with osteosarcoma, including financial difficulties, patients’ feeling of social isolation by their peers, and role transition; therefore, the anxiety and depression of the parents might continue to deteriorate. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation